2020
DOI: 10.1039/d0ra08295c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and functionalization of 3D-printed soft and hard scaffolds with growth factors for enhanced bioactivity

Abstract: 3D printed scaffolds with tailored bioactivity using protein conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…Feng et al [ 66 ] also reported increased intensity of nitrogen peak with increase in modification time from XPS results of polydopamine‐coated polycaprolactone scaffolds. The observation of nitrogen peak confirmed the deposition of polydopamine coating and similar results have been reported by Jose et al [ 67 ] and Liao et al [ 68 ]…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Feng et al [ 66 ] also reported increased intensity of nitrogen peak with increase in modification time from XPS results of polydopamine‐coated polycaprolactone scaffolds. The observation of nitrogen peak confirmed the deposition of polydopamine coating and similar results have been reported by Jose et al [ 67 ] and Liao et al [ 68 ]…”
Section: Resultssupporting
confidence: 90%
“…Feng et al [66] also reported increased intensity of nitrogen peak with increase in modification time from XPS results of polydopamine-coated polycaprolactone scaffolds. The observation of nitrogen peak confirmed the deposition of polydopamine coating and similar results have been reported by Jose et al [67] and Liao et al [68] The nitrogen content obtained for polydopaminecoated PLA specimens with infill density of 100% immersed in 2 mg/ml concentrated coating solution for 7 h was certainly 35.67% lower than that obtained for polydopamine-coated PLA specimens with 50% infill density immersed for 7 h. Thus, it can be said that infill density plays a major role in successful deposition of coating as coating material was more effective in getting through the pores of PLA specimen with 50% infill density.…”
Section: Surface Morphologysupporting
confidence: 91%
“…has been widely accepted in the design of hydrogels. 6,7 Among these biopolymers, gelatin is an attractive candidate as starting material for bio-hydrogel preparation thanks to its non-cytotoxicity, good biocompatibility, low antigenicity, easy degradation and unique gelling properties. 8 Gelatin is a proteinaceous material obtained by partial hydrolytic degradation of naturally occurring collagen, which is known to be the most abundant protein in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs and biomolecules carrying thiol and amine groups are easily bound to the surface of the PDA-coated materials by the chemical and physical reaction with catechols of PDA. [43][44][45][46][47] Some studies have veried that growth factors such as BMP-2, bFGF, insulin-like growth factor 1 (IGF-1) can be effectively bound on the surface of aliphatic polyester scaffold using PDA coating mainly via covalent bond and possible hydrogen bond. [48][49][50][51][52][53][54] Surface modication of PDA coating is a simple one-step method that does not need special facilities and maintains the structure of the scaffold material.…”
Section: Surface Coating Combined With Covalent Binding Methodsmentioning
confidence: 99%